IMPORT DEPENDENCY ON INTERMEDIATE GOODS IN TURKEY: AN INPUT-OUTPUT ANALYSIS - Ünal, Emre (My University, 2020)
In this study, import dependency on intermediate goods within mainmanufacturing industries in Turkey was analyzed using World Input-Output Database (WIOD) between 2002 and 2014. Moreover, importdependency on intermediate goods within consumption goods sector wascompared to that within export goods sector using a weighted multipliersapproach. The analysis shows that Turkey’s import dependency on intermediategoods increased significantly in this period. The computer, electronic andoptical products and automotive industries showed a markedly high importdependency on intermediate goods. The main reason for the import dependencyin the automotive industry was the fact that; almost all goods produced wereexported. The computer, electronic and optical products industry experiencedhigh import dependency on intermediate goods, whereas the ratio of exportto total output gradually declined and domestic consumption increased.The research reveals that after the 2000-2001 Economic Crisis, a number ofinstitutional factors promoting a liberal economy and thus attracting FDI,stimulated the productivity growth of export goods. Thus, export growth wasfollowed by high import dependency in export goods.
Keywords: Mühendislik; Elektrik ve Elektronik; Mühendislik; Makine; Endüstri Mühendisliği; Mühendislik; Kimya; İktisat